2013
DOI: 10.1109/tasc.2013.2239691
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Performance of a Laser Structured YBCO Tape Suitable for Insertion Devices Technology

Abstract: Recent intensive development of high-temperature superconducting (HTS) materials resulted in the availability of various commercial HTS tapes, in particular coated conductors. Technological progress in this field and up-coming market will reduce the costs of the tape. One very promising application for free electron laser technology considers a new concept of meander-like structured stacked HTS tapes to provide the desired magnetic field pattern with periodic changing field orientation. For the first time, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The advantage of the laser-scribing technique is that it is fast and cost effective because the tape can be structured at ambient atmosphere without special chemical treatments, as required in the lithography process. Moreover, it has been already proved that this technique does not degrade the J c of the tape [14,24]. For these reasons a computer controlled TRUMPF IR YAG laser-scribing system utilizing picoseconds laser pulses with a beam width w b of only 25 μm and a positioning precision of ±3 μm, is considered [23].…”
Section: Laser-scribed Hts Tapementioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of the laser-scribing technique is that it is fast and cost effective because the tape can be structured at ambient atmosphere without special chemical treatments, as required in the lithography process. Moreover, it has been already proved that this technique does not degrade the J c of the tape [14,24]. For these reasons a computer controlled TRUMPF IR YAG laser-scribing system utilizing picoseconds laser pulses with a beam width w b of only 25 μm and a positioning precision of ±3 μm, is considered [23].…”
Section: Laser-scribed Hts Tapementioning
confidence: 99%
“…Therefore, we propose using a parallel shunt resistance R S , acting as a passive quench protection to the HTS tape. We have shown that such a shunt is capable to overtake a huge portion of the high over-currents (up to ∼1.4×I c ) without harming the tape [14]. Regarding the quench protection of any superconducting coil, a self-inductance of the coil is an important parameter since it influences quench behavior significantly.…”
Section: Quench Protectionmentioning
confidence: 99%
“…This concept which offers advantages for short periods (< 10 mm) and narrow gaps, could be used for table top FELs. The first magnetic field measurements of a 12 mm wide HTS structured tape have been successfully performed in CASPER I (liquid helium bath) with a Hall probe [8].…”
Section: Hts Stacked Undulator For Table Top Felmentioning
confidence: 99%
“…The scheme developed includes partial insulation on the part of the magnet far from the beam to reduce the field settling time, relevant for tuning the undulator with an electron beam, keeping J e as high as for a non insulated magnet.Another proposal for a HTS tape stacked undulator has been made for free electron laser applications [6]. To define the current path allowing a sinusoidal magnetic field on axis, the HTS tape is structured, which can be performed using lithography [6] or a high power laser [7]. For such an application, uniformity of the current along the conductor is a must to reach the high field quality necessary for an undulator.Important issues to be addressed for the application of HTS tape to accelerator magnets are quench detection and protection, as well as radiation hardness.…”
mentioning
confidence: 99%
“…Another proposal for a HTS tape stacked undulator has been made for free electron laser applications [6]. To define the current path allowing a sinusoidal magnetic field on axis, the HTS tape is structured, which can be performed using lithography [6] or a high power laser [7]. For such an application, uniformity of the current along the conductor is a must to reach the high field quality necessary for an undulator.…”
mentioning
confidence: 99%